Pengembagan Media Pembelajaran Monopoli Pop-Up pada Mata Pelajaran Matematika Materi Bangun Ruang Kelas V Di SDN Mlajah 1 Bangkalan - Nina Rosiana; Rika Wulandari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The pop-up Monopoly is a learning medium in the form of a Monopoly game equipped with several elements such as pop-up books and some cards. The pop-up Monopoly media in mathematics, especially in the subject of spatial shapes, aims to enhance students' enthusiasm in learning every mathematical activity, thereby changing students' perception that mathematics learning is boring and uninteresting. Thus, a new innovation was designed as an effort to develop a concrete medium in the form of a pop-up Monopoly, making learning more engaging and less boring. The purpose of this research is to determine the level of validity, effectiveness, and attractiveness of the pop-up Monopoly media for spatial shapes. This research uses R&D with the ADDIE research model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. This development research uses research instruments in the form of interview guidelines, observation sheets, questionnaires, and tests. The validity of the product was obtained from media expert validators at 92% with a very valid category, learning material experts at 89% with a very valid category, and learning design experts at 93% with a very valid category. The effectiveness of the product was obtained from teacher observation sheets, student observation sheets, and student learning outcome tests. Based on the results of this study, the pop-up monopoly media for spatial building materials is valid, interesting, and effective for use in fifth-grade mathematics classes.